Pengaruh Kinerja Keuangan Terhadap Tanggung Jawab Sosial Perusaahaan (Corporate Social Responsibility) Pada Perusahaan Tambang Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2016 - Koloay, Natalia; Montolalu, Johny; Mangindaan, Joanne V. (Sam Ratulangi University, 2018)
Corporate social responsibility (CSR) is one form of awareness of a company to the environment. Currently CSR aims to maximize profits but is also required to better accommodate the needs of the community and its stakeholders. This study aims to determine the effect of Return on assets, Return on equity, and Net profit margin on social responsibility at mining companies listed in the Indonesia Stock Exchange period 2015-2016. This research uses multiple regression analysis method. The results of this study indicate that during the period 2015-2016 ROA has no significant effect on CSR with a significant value of 0.986, ROE has no significant effect on CSR with a significant value of 0.191, and NPM has no significant effect on CSR with a significant value of 0.205.